2006
DOI: 10.1007/s11284-006-0034-8
|View full text |Cite
|
Sign up to set email alerts
|

Coarse woody debris mass and nutrients in forest ecosystems of Korea

Abstract: Coarse woody debris (CWD) is an essential component of forests. However, quantification of both the mass and nutrient content of CWD within a given environment tends to be a fairly labor-intensive proposition that requires long-term studies to be conducted for viable data to be obtained. As a result, various aspects of CWD in forest ecosystems remain somewhat poorly understood. In this review, we have compiled all available estimates of CWD mass and nutrients from both coniferous and deciduous forests in Korea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 38 publications
2
18
1
Order By: Relevance
“…CWD potentially affects soil cycling through the dissolving of organic C which would lead to N immobilization (Mattson et al, 1987;Fierer et al, 2001;Spears et al, 2003;Hafner and Groffman, 2005). N and P stocks in CWD were similar to those reported in other studies (Idol et al, 2001;Currie and Nadelhoffer, 2002) while higher than the research studied in a natural mixed deciduous forest in Korea (Kim et al, 2006). The results suggested that the ecological value of CWD for C and nutrients cycling was relatively important.…”
Section: And Nutrient Contentssupporting
confidence: 85%
“…CWD potentially affects soil cycling through the dissolving of organic C which would lead to N immobilization (Mattson et al, 1987;Fierer et al, 2001;Spears et al, 2003;Hafner and Groffman, 2005). N and P stocks in CWD were similar to those reported in other studies (Idol et al, 2001;Currie and Nadelhoffer, 2002) while higher than the research studied in a natural mixed deciduous forest in Korea (Kim et al, 2006). The results suggested that the ecological value of CWD for C and nutrients cycling was relatively important.…”
Section: And Nutrient Contentssupporting
confidence: 85%
“…CWD C storage was 0.11, 0.04 and 0.68 t C ha -1 in the 30-, 44-, and 71-year-old stands, respectively, while N storage in this study was lower than the range (0.005-0.024 t N ha -1 ) previously reported for deciduous species by Kim et al [37]. Stand age, density and basal area had no effect on C and N storage in the forest floor.…”
Section: Cwd and Forest Floorcontrasting
confidence: 83%
“…All pieces of CWD with a base diameter greater than 5 cm at the break point were tagged and their species, type (stump, snag, and downed dead wood), diameters (base, middle, and top), and length were recorded in the field. The decay class was also classified into five different levels (I-V) according to a CWD decay classification system [33], which was modified from the original criteria [34,35]. The classification system classifies CWD by the presence or physical condition of the bark, as well as by the degree of twig retention, structural integrity, and root penetration.…”
Section: Tree Morality Cwd Volume and Massmentioning
confidence: 99%